The coastal community views on the environmental changes - Idris, Khairuddin; Abu Samah, Asnarulkhadi; Suandi, Turiman; Abu Samah, Bahaman; Muhammad, Mahazan; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
This study aims to explore coastal community views on the environmental changes. Their views are covering four aspects, their awareness, the causes, the impacts and things they have done to absorb the impacts. The data were gained via three FGDs conducted with the coastal community at Kuala Besut, Tanjung Piai and Lumut. Based on the FGDs, it can be concluded the coastal community is aware of the changes and they claimed these changes are mainly caused by two sources – the human and the natural factors. The changes are predominantly impacting them in negative ways and require them to have some initiatives to apprehend the impacts. A number of recommendations are highlighted and hopefully, it can guide the concern parties in constructing related strategies that can assist the coastal community in lessening the impacts of the environmental changes.